The heterogeneity of genomic alterations, metastatic patterns and immune microenvironment in metastatic ovarian cancer originating from colorectal cancer - Chen, Chao; Wang, Jian; Sun, Binjie; Zheng, Yuyan; Ge, Xiaoxu; Gong, Zhiyuan; Gu, Haochen; Zhang, Zhiwei; Zhu, Akao; Shao, Yingkuan; Hu, Yeting; Ma, Lijia; et al. (Frontiers in Immunology, 2025)
PurposeThe ovarian metastases originating from colorectal cancer (CRCOM) develops rapidly and lethally. Previously, the genetic alterations and metastatic pathway in CRCOM were not well understood. The aim of this study is to explore the special molecular phenotype and dissemination patterns of CRCOM.MethodsThe whole-exome sequencing (WES) was performed on 65 matched tissue samples from 11 CRCOM patients, including 11 primary colorectal cancer (CRC) with 11 matched normal tissues, and 43 multi-site metastases (including 15 CRCOMs and 4 patients had bilateral ovarian metastases (OMs). Genetic landscape, neoantigens, tumor clonal origin and spread of CRCOMs were analyzed. TCGA-COAD dataset combined with our data were used for survival analysis and validation of the findings.ResultsThere was significant intertumoral heterogeneity among patients with CRCOM and intra-tumoral heterogeneity among multiorgan metastases. 19 genes were inferred as the potential driver genes of CRCOM. USP7 and RPA1 were HRD-related mutations and potential to serve as predictive biomarkers in OM. The putative neoantigen number of the primary CRC and OM varies widely among patients. The OM showed an immune desert state, extremely deficient in each subtype of immune cells. According to COSMIC signatures features, the CRCOM patients were divided into two groups, which are different in overall survival (OS) (median OS, 720 days vs 360 days, P = 0.074) and genetic alterations. Two metastatic patterns of CRCOM were summarized, which were primary CRC to OM, and metastases to metastases (including lymph node metastases (LNM) to OM, peritoneal metastases (PM) to OM, and other metastases to OM). Interestingly, the sources of bilateral OM might be different in the two patients.ConclusionThis study presents a better understanding the heterogeneity of the genetic characterizations and metastatic pattern in CRCOM. The subtypes of CRCOM with USP7 mutation, more copy number alterations, lower neoantigens, and immunoscore have a worse prognosis.